2011
DOI: 10.1007/s00586-011-2070-5
|View full text |Cite
|
Sign up to set email alerts
|

Iliac crest orientation and geometry in able-bodied and non-treated adolescent idiopathic scoliosis girls with moderate and severe spinal deformity

Abstract: Purpose To identify pelvic rotation and/or distortion in able-bodied and untreated AIS girls with moderate and severe scoliosis and verify association of pelvic morphological changes with Cobb angle increase. Methods The 3D coordinates of nine anatomic bony landmarks were identified to estimate pelvic orientation using a Flock of Birds system. The distances between the first sacral vertebral body (S1) and each of the eight iliac spine landmarks in all three planes were calculated to identify pelvic distortion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 26 publications
5
37
0
Order By: Relevance
“…They assume that a pelvic rotation-inducing system transfers this torsion to the spine without providing further explanations. Based on a correlation between Cobb angle progression and iliac spine asymmetries, Stylianides et al [24] proposed that an asymmetrical bone growth in the iliac crest could generate horizontal torsion of the pelvis described by Burwell et al [23]. Our 3D radiographic study supports this assumption because asymmetries were noted in different locations on the coxal bones.…”
Section: Vertebral Wedging and Pelvic Asymmetry Associationsupporting
confidence: 91%
See 3 more Smart Citations
“…They assume that a pelvic rotation-inducing system transfers this torsion to the spine without providing further explanations. Based on a correlation between Cobb angle progression and iliac spine asymmetries, Stylianides et al [24] proposed that an asymmetrical bone growth in the iliac crest could generate horizontal torsion of the pelvis described by Burwell et al [23]. Our 3D radiographic study supports this assumption because asymmetries were noted in different locations on the coxal bones.…”
Section: Vertebral Wedging and Pelvic Asymmetry Associationsupporting
confidence: 91%
“…Mahaudens et al [50] reported thicker iliac crests in AIS than in nonscoliotic individuals. Asymmetries were also reported between the right and left AIS iliac crest widths and depths compared with nonscoliotic girls [24]. Our results are the first to document radiographic pelvic 3D asymmetries at the very onset of the scoliosis and the persistence of these with as scoliosis progresses.…”
Section: Pelvic Asymmetrysupporting
confidence: 62%
See 2 more Smart Citations
“…The overall mean of this motion was −0.12 ± 2.48°(mean ±SD) with values ranging from −4.30°to 5.72° (Table 1). Subjects were arbitrarily divided according to the median as the division point, as in previous studies [1,26,27]. Those with the lower values (0.86 ± 0.71°) were assigned to the small range of trunk bending; the remaining subjects were assigned to the large range (3.12 ± 1.01°).…”
Section: Methodsmentioning
confidence: 99%